Assessing the Potentials of Digitalization as a Tool for Climate Change Adaptation and Sustainable Development in Urban Centres - Balogun, A.-L. (Elsevier Ltd, 2020)
Digitalization is a key enabler of sustainable development of citiesâ socio-economic dynamics with the potential to foster climate-friendly urban environments and societies. The advent of the 4th industrial revolution has seen the increased application of digitalization in several fields and at different levels. High-tech digital devices, platforms and environments are increasingly being deployed to enhance productivity, efficiency and sustainability, and improve overall well-being of urban dwellers. Digitalization is projected to further impact cities in future, transform jobs and trigger life-style changes with far-reaching impacts that will ultimately affect citiesâ resilience and adaptation capacities. While a growing body of research has highlighted the significance of digitalization to climate change mitigation such as reducing GHG and CO2 emissions, comprehensive evaluations of the potentials of digitalization as an enabler of climate change adaptation remain scarce. This paper addresses this gap by analysing the current trend in digital revolution in relation to climate change adaptation and examines the likely challenges of digitalization. A desk research method was adopted, focusing on core digitalization concepts driving the Fourth Industrial Revolution (IR 4.0). Nine case studies in cities across various continents were selected to assess the potentials of digitalization in addressing climatic hazards and to highlight benefits from implementing digitalization, while considering the social-ecological-technological challenges and tensions around IR 4.0. Our findings reveal the capabilities of digitalization in supporting more effective early warning and emergency response systems, enhancing food and water security, improving power infrastructure performance, enabling citizen engagement and participatory adaptation measures and minimizing the impacts of climatic hazards. Finally, we recommend feasible pathways to overcome present risks and challenges in order to optimize the numerous opportunities offered by digitalization in support of climate change adaptation initiatives. Â© 2019 Elsevier Ltd